Optimization of Genomic DNA Extraction Method on Nutmeg (Myristica fragrans Houtt.) - Tanti Agustina; Abdul Razaq Chasani (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Nutmeg (Myristica fragrans) is one of the commodities in the Myristicaceae family that has numerous benefits and has high phenolic compounds. Elevated amounts of secondary metabolites in the Myristica genus pose significant challenges for obtaining high-quality DNA. This complexity often results in reduced DNA recovery and suboptimal absorbance ratios, attributed to contamination by RNA and proteins in DNA extraction yields.. The results of DNA extraction that have been obtained through several variations of optimized methods are compared. The DNA extraction method using a modified Geneaid Genomic DNA Mini Kit was determined to produce the highest quality and quantity of DNA. Compared to other protocols such as Doyle and Doyle, modified Doyle and Doyle, and the basic protocol of the Geneaid kit without improvement, the modified Geneaid Genomic DNA Mini Kit had a high mean range purity of 1.83, and bands appeared.